BLENDED LEARNING: POSSIBILITIES APPLICATION IN THE TECHNOLOGICAL UNIVERSITY OF CANCUN - Pérez De la Cruz, Antonio (2011)
At present the present time the skill related to the Technologies of Information and Communication (TIC´s) acquiere every day more importance in the contribution to business success, mainly in the area of formation of human capital, in which in-line education trends. For this reason, the universities must begin to implement education model in-line learning, combined with the actual clases, with the objective that the students acquire experience in the use of the TIC´s. In consecuence, the present investigaction provides an approach to the model of b-learning to explain what elements are included and the studen and teacher`s roll, as well as to Know the possibilities for its implementation and identifying, initially, if we count with the necessary resources, means, knowledge and interest in the use of the TIC´s in the processes of an already realised study of eduction and student of Business Administration of the Divisiñon Económico administrativa of the Universidad Tecnológica de Cancún. And finally to reach conclusions and recommendations for its application.